Analisis Efisiensi Teknis dan Preferensi Petani Menghadapi Risiko Produksi Usahatani Kentang : Penelitian - Simanullang, Lora Wain Natalia Putri; Nainggolan, Saidin; Indah, Vika (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Potato farming in Kayu Aro Barat District, Kerinci Regency, Jambi Province, is a major agricultural commodity with significant potential, but its productivity has not yet reached optimal levels. Factors influencing potato production include inefficient input usage, seed quality, and reliance on costly production inputs. This study aims to analyze the technical efficiency in potato farming and the farmers' preferences in managing production risks. The research employs a quantitative approach with descriptive and analytical methods, collecting data through interviews, observations, and questionnaires from farmers in Kayu Aro Barat District. The results show that seeds, fertilizer, and labor significantly affect potato production, while land area and pesticides have no significant statistical impact. Additionally, most farmers exhibit a